2007
DOI: 10.1118/1.2431473
|View full text |Cite
|
Sign up to set email alerts
|

Spread‐out Bragg peak and monitor units calculation with the Monte Carlo Code MCNPX

Abstract: The aim of this work was to study the dosimetric potential of the Monte Carlo code MCNPX applied to the protontherapy field. For series of clinical configurations a comparison between simulated and experimental data was carried out, using the proton beam line of the MEDICYC isochronous cyclotron installed in the Centre Antoine Lacassagne in Nice. The dosimetric quantities tested were depth-dose distributions, output factors, and monitor units. For each parameter, the simulation reproduced accurately the experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 17 publications
1
36
0
Order By: Relevance
“…Other approaches use Monte Carlo methods. [7][8][9] In this study, we use sampling measurement data to predict proton beam parameters using a modification of Eq (1) and present our obtained results. The proton beam therapy system parameters, such as beam current, range at nozzle, scatter, and RM, are set using a conversion algorithm to produce the range and SOBP for each patient.…”
Section: Introductionmentioning
confidence: 96%
“…Other approaches use Monte Carlo methods. [7][8][9] In this study, we use sampling measurement data to predict proton beam parameters using a modification of Eq (1) and present our obtained results. The proton beam therapy system parameters, such as beam current, range at nozzle, scatter, and RM, are set using a conversion algorithm to produce the range and SOBP for each patient.…”
Section: Introductionmentioning
confidence: 96%
“…The suitability of the MCNPX code for simulating therapeutic absorbed dose distributions and secondary radiation related to proton therapy has been established (Fontenot et al 2005, Herault et al 2005, Tayama et al 2006, Herault et al 2007, Zheng et al 2007). …”
Section: Monte Carlo Modeling Of the Treatment Unitmentioning
confidence: 99%
“…With an accurate Monte Carlo simulation of the beamline, authors have reported a good agreement between calculated and measured proton dose distributions (Paganetti et al, 2004;Hérault et al, 2005;Newhauser et al, 2005;Polf et al, 2007;Martinetti et al, 2009;Stankovskiy et al, 2009). Recent literature even suggests using Monte Carlo methods in clinical proton therapy applications (Hérault et al, 2007;Paganetti et al, 2008). In fact, clinical treatment planning systems are based on a parameterisation of measured proton distributions and therefore they suffer from approximations in modelling particle transport physics.…”
Section: Introductionmentioning
confidence: 99%